In vitro analysis of Fusarium head blight resistance in ancient Syrian wheats (Triticum sp.) - Sakr, Nachaat (The Indian Journal of Agricultural Sciences, 2020)
Assessment of Fusarium head blight (FHB) resistance in ancient wheat (Triticum sp.) cultivars is crucial for disease management. To update our knowledge, in vitro resistance in two ancient Syrian bread and durum wheat cultivars with known resistance to four Fusarium species was investigated at Plant Protection Lab., Damascus under Atomic Energy Commission of Syria during 2019. Three criteria involved in a Petri-dish test were compared on wheat plants. Cultivar differences at seedlings stage after inoculation with a set of 16 Fusarium isolates relative to the controls were detected. Standardized area under disease progress curve (AUDPCstandard) did differentiate the two wheat cultivars; however, seed germination rate reduction and coleoptile length reduction did not. Inter- and intraspecific differences were observed in pathogenicity of four Fusarium species toward wheat plants. Less AUDPCstandard was related to greater FHB disease-type I and -type II resistance previously generated under controlled conditions. In vitro data confirmed artificial head and floral inoculations in which the bread wheat cultivar was less affected to FHB infection than durum wheat. The ancient Syrian wheat plants may be introduced into wheat breeding programs because of their resistance to FHB.